Targeting the Bcl-2 Family in B Cell Lymphoma - Adams, Clare M.; Clark-Garvey, Sean; Porcu, Pierluigi; Eischen, Christine M. (Frontiers in Oncology, 2019)
Although lymphoma is a very heterogeneous group of biologically complex malignancies, tumor cells across all B cell lymphoma subtypes share a set of underlying traits that promote the development and sustain malignant B cells. One of these traits, the ability to evade apoptosis, is essential for lymphoma development. Alterations in the Bcl-2 family of proteins, the key regulators of apoptosis, is a hallmark of B cell lymphoma. Significant efforts have been made over the last 30 years to advance knowledge of the biology, molecular mechanisms, and therapeutic potential of targeting Bcl-2 family members. In this review, we will highlight the complexities of the Bcl-2 family, including our recent discovery of overexpression of the anti-apoptotic Bcl-2 family member Bcl-w in lymphomas, and describe recent advances in the field that include the development of inhibitors of anti-apoptotic Bcl-2 family members for the treatment of B cell lymphomas and their performance in clinical trials.